Assessing the Value of Antibiotics on Farms: Modeling the Impact of Antibiotics and Vaccines for Managing Lawsonia intracellularis in Hog Production - Jansen, Travis; Weersink, Alfons; von Massow, Michael; Poljak, Zvonomir (Frontiers in Veterinary Science, 2019)
Increasing awareness of antibiotic resistance has correspondingly increased efforts to identify and reduce the causal behaviours that led to this severe public health threat. The consequences of these efforts are regulatory and market pressures limiting antibiotic use by livestock farmers which may lead to significant financial and welfare challenges on the farm, even if antibiotics can be substituted by vaccines. The purpose of this study is to measure the relative cost-effectiveness of antibiotics versus vaccines for controlling L. intracellularis on a Canadian farrow-to-finish pig farm. This is done by modelling the production and economic impact of different antibiotics and vaccines available for managing this disease, listed in the Canadian Compendium of Veterinary Products. The economic impacts (in Canadian dollars) of the disease are estimated and the net benefits of alternative prevention and treatment options are compared to determine the relative cost-effectiveness of each strategy. Of the twelve options analyzed, four were preventative (antibiotic and vaccine) and eight were antibiotic treatments. Prophylactic chlortetracycline (an antibiotic) is the most cost-effective option for managing L. intracellularis, while Porcilis Ileitis (a vaccine) is the least cost-effective strategy. This result remains robust considering sensitivity analysis of the production parameters, which indicates that preventative antibiotics are more cost-effective than vaccines. This implies that banning preventative antibiotic treatments harms the bottom line of farmers under current market conditions.